Strength and durability enhancement of low carbon gel concrete - Yang Jia; Jianfeng Zhang; Ya Cao; Shiqi Liu; Zichen Zhou; Mingxia Li (PLoS ONE, 2025)
In order to reduce the difficulty of concrete preparation, reduce the environmental hazards caused by concrete materials and their preparation process, and meet the development trend of energy saving and emission reduction, this study proposes a low-carbon gel material composed of slag powder, fly ash and gypsum for concrete preparation. Low-carbon gel concrete was made with the ingredients of slag powder, fly ash and gypsum with a water-cement ratio of 0.38 and a ratio of slag powder to fly ash of 1:1.The compressive, flexural and tensile strengths of low-carbon gel concrete samples with different ratios were tested by standard concrete strength test methods to assess their durability properties, and the effects of different ratios of slag powder, admixture and gypsum on the material properties of low-carbon gel were analyzed. concrete material properties with different proportions of slag powder, admixtures and gypsum were analyzed. The experimental results showed that low-carbon gel concrete materials outperformed traditional concrete materials in terms of compressive strength, flexural strength, and tensile strength. After 28 days of curing, the compressive strength of low-carbon gel concrete was 20% higher than that of conventional concrete, and the carbonation depth was reduced by 30.77%. The results indicate that the low-carbon gel concrete materials proposed in this study have excellent strength and durability, and can improve the performance of conventional concrete. This material provides a green and sustainable solution for the modern construction industry, contributing to the sustainable development of the construction sector and the global fight against climate change.